ANTIMICROBIAL STUDY OF WHOLE EXTRACT, ISOLATED INGREDIENT, AND NEWLY SYNTHESIZED ANALOGUE FROM LEAVES EXTRACT OF CASSIA ABSUS PLANT - M. O. MALPANI; P. R. RAJPUT (International Journal of Pharma and Bio Sciences, 2013)
Medicinal trees play a significant role in our National economy. Melghat region is a rich source of medicinal flora. Tectona grandis (teak) is the most dominant species, located in the northern part of Amravati District of Maharashtra State in India. The association of plant species to Tectona grandis depends upon latitude, gradient and other physiographic feature of the habitat. Near about 772 natural species found in Melghat region which are being used by the tribal residents over the centuries for the cure of various skin diseases.Cassia absus is one of the medicinally potential plants found in Melghat region which is frequently used for the eradication of skin diseases. The present investigation was undertaken to screen the efficacy of Cassia absus leaves aqueous extract, isolated acidic ingredient and its newly synthesized amide analogue on certain bacteria and fungi which are responsible for skin diseases such as Streptococcus pyogenes, Nocardia calcarea, Bacillus subtilis, Pseudomonas aeruginosa, Trichosporon cutaneum, and Rhodotorula rubra. In comparison among the impact of test compounds; it was revealed that, the Cassia absus leaves isolated acidic ingredient and its newly synthesized amide analogue showed significant activity than the whole aqueous extract of leaves.